PENDAMPINGAN SOSIALISASI PERPAJAKAN UNTUK MENINGKATKAN KESADARAN DAN KEPATUHAN DALAM PELAPORAN PAJAK BAGI UMKM KOTA BOGOR - Yuliandi Yuliandi; Arnold Sultantio Hutabarat; Amrulloh Amrulloh (LPPM Institut Pendidikan Nusantara Global, 2025)
This Community Service is an activity of a lecturer from Institut Bisnis dan Informatika Kesatuan (IBIK) Bogor with a Micro Small and Medium Enterprise (MSME) actor, namely Sweet & Tasty. The aim of this activity is to encourage awareness and compliance in tax reporting. This activity is carried out as feedback from the needs analysis action (need survey) that has been carried out by the IBIK team with Sweet & Tasty. We applied two methods for our activity, first, we provided an explanation to improve their literacy about taxes, and second, in a sharing session, we emphasized the importance of tax reporting. The program's implementation method included a live lecture explaining tax concepts, the tax reporting process, and the benefits of tax compliance for business sustainability. Additionally, an interactive discussion session was included to provide participants with a consultation space regarding any tax issues they faced. The results of the program demonstrated an increase in participants' understanding of tax obligations and awareness of the importance of tax reporting as part of good business governance. This program is expected to encourage MSMEs to be more compliant with tax administration, thereby strengthening their business credibility and sustainability.